Neural circuits for decision-making based on pineal photoreception in zebrafish - Seiji Wada; Yuki Yamamoto; Tomoka Saito; Masahiko Hibi; Mitsumasa Koyanagi; Akihisa Terakita (Proceedings of the National Academy of Sciences, 2026)
Nonmammalian vertebrates possess photosensitive pineal organs. We previously found that in the zebrafish pineal organ, photoreceptor cells expressing parapinopsin 1 (PP1), a bistable opsin, exhibit “chromatic” responses to ultraviolet (UV) and visible light through a unique mechanism based on the photo-interconvertibility between UV-sensitive (inactive) and visible light-sensitive (active) states of PP1. However, it remains unclear whether PP1-based chromatic responses are transmitted to pineal ganglion cells and further to the brain. In this study, we designed light stimuli by exploiting the spectral properties of the two states of PP1 and found that pineal ganglion cells exhibited chromatic responses, characterized by opposing changes to UV and visible light, using calcium imaging. These responses were significantly reduced in PP1-deficient fish compared to wild-type fish, indicating that PP1-derived signals are transmitted to pineal ganglion cells. This spectral stimulation approach enables selective analysis of PP1-specific responses. Using these stimuli, we further identified the tegmentum as a central brain region receiving pineal-derived “color” information, although it is also indirectly influenced by retinal photoreception. Both PP1-deficient fish and tegmentum neuron-ablated fish showed impaired vertical movements in response to sequential wavelength component changes. These results suggest that the neural circuit from the pineal organ to the tegmentum, which processes PP1-based chromatic information, contributes to the decision-making process for wavelength-dependent vertical behavior that is also driven by visual input. These findings provide insights into the neural circuits integrating pineal and retinal light information and how PP1-based color opponency affects behavior via tegmentum neurons.